Pengaruh Penerapan Model Pembelajaran Kooperatif terhadap Kemampuan Bekerja Sama, Komunikasi, dan Hasil Belajar pada Siswa di Kelas 2 SD Negeri 31 Muaro (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effect of the application of the cooperative learning model on the ability to collaborate, communicate, and student learning outcomes in grade 2 of SD Negeri 31 Muaro. This study uses a qualitative approach with the interview method as the main data collection technique. Information was obtained through in-depth interviews with classroom teachers who have applied the cooperative learning model in the learning process. The results of the study show that the application of the cooperative learning model has a positive impact on students' ability to work together, improve communication skills between students, and contribute to improving student learning outcomes in general. Teachers state that students become more active, help each other in groups, and are more courageous to express their opinions. These findings indicate that the cooperative learning model can be an alternative effective learning strategy to improve the social and academic aspects of students at the elementary school level.